Biomimetic design and fabrication of multilayered osteochondral scaffolds by low-temperature deposition manufacturing and thermal-induced phase-separation techniques. (23rd May 2017) - Zhang, Ting; Zhang, Hefeng; Zhang, Laquan; Jia, Shuaijun; Liu, Jian; Xiong, Zhuo; Sun, Wei
Abstract: Integrative osteochondral repair is a useful strategy for cartilage-defect repair. To mimic the microenvironment, it is necessary that scaffolds effectively mimic the extracellular matrix of natural cartilage and subchondral bone. In this study, biomimetic osteochondral scaffolds containing an oriented cartilage layer, a compact layer, and a three-dimensional (3D)-printed core-sheath structured-bone layer were developed. The oriented cartilage layer was designed to mimic the structural and material characteristics of native cartilage tissue and was fabricated with cartilage matrix-chitosan materials, using thermal-induced phase-separation technology. The 3D-printed core-sheath structured-bone layer was fabricated with poly(L-lactide-co-glycolide)/ β -tricalcium phosphate-collagen materials by low-temperature deposition technology, using a specially designed core-sheath nozzle, and was designed to mimic the mechanical characteristics of subchondral bone and improve scaffold hydrophilicity. The compact layer was designed to mimic the calcified-layer structure of natural cartilage to ensure the presence of different suitable microenvironments for the regeneration of bone and cartilage. A dissolving-bonding process was developed to effectively combine the three parts together, after which the bone and cartilage scaffolds exhibited good mechanical properties and hydrophilicity. Additionally, goat autologous bone mesenchymal stem cells (BMSCs) were isolated and then seeded into the bone and cartilage layers, respectively, and following a 1 week culture in vitro, the BMSC-scaffold constructs were implanted into a goat articular-defect model. Our results indicated that the scaffolds exhibited good biocompatibility, and 24 weeks after implantation, the femoral condyle surface was relatively flat and consisted of a large quantity of hyaloid cartilage. Furthermore, histological staining revealed regenerated trabecular bone formed in the subchondral bone-defect area. These results provided a new method to fabricate biomimetic osteochondral scaffolds and demonstrated their effectiveness for future clinical applications in cartilage-defect repair.